The Temporal Gap Between Evaluation and Monitoring: Re-thinking the Design of M&E Systems - Kalanda, Boniface Francis (Advances in Social Sciences Research Journal, 2026)
Evaluation is widely recognized as a critical tool for accountability and strategic learning. Yet evaluations are infrequent, retrospective, and resource-intensive. In my cases, by the time findings are available, organizations often have already adapted based on real-time monitoring data. This paper argues that while evaluations remain indispensable for long-term impact assessment and external accountability, monitoring processes are the primary drivers of organizational learning in practice. Drawing on literature from programme evaluation, organizational learning, and adaptive management, the paper highlights the temporal gap between evaluation and monitoring. It explores case examples from development, education, and health sectors, and proposes a reframing of evaluation’s role in contemporary organizations. The analysis concludes that monitoring drives real-time adaptation, while evaluation provides retrospective validation, and that organizations must integrate both to maximize learning